Reduction-responsive supramolecular hybridized paclitaxel nanoparticles for tumor treatment - Wang, Yuhan; Cui, Yingli; Dai, Tinggeng; Yue, Ying (Frontiers in Bioengineering and Biotechnology, 2023)
Powerful chemotherapeutics have been used to combat tumor cells, but serious adverse effects and poor therapeutic efficiency restrict their clinical performance. Herein, we developed reductionresponsive supramolecular hybridized paclitaxel nanoparticles (PTX@HOMNs) for improved tumor treatment. The nanocarrier is composed of F127 and strengthened by a disulfide bond linked organosilica network, which ensures the desirable stability during blood circulation and controlled drug release at tumor sites. The as-prepared PTX@HOMNs could effectively accumulate at tumor regions. After entering tumor cells, PTX@HOMNs can respond to intracellular glutathione, and trigger active drug release for chemotherapy. As a result, PTX@HOMNs exhibited potent antitumor activity against ovarian tumors in vitro and in vivo. Our work provides a deep insight into constructing simple and controlled drug delivery nanoplatforms for improved tumor treatment.